Reliability analysis for dependent competing failure processes with changing degradation rate and hard failure threshold levels. (April 2018) - Hao, Songhua; Yang, Jun
Highlights: We develop a model with changing degradation rate and hard failure threshold levels. Harmful shocks affect both temporal degradation performance and degradation rates. The threshold level in extreme shock model is decreased by arrived harmful shocks. The threshold level in δ -shock model depends on the magnitude of the previous shock. Abstract: Many systems are often subject to degradation and random shocks simultaneously, and their failure is the competing results of soft and hard failures. Motivated by the example of reinforced concrete (RC) pier columns of sea bridges, which experience dependent corrosion process and vessel collision-induced random shocks, shocks are divided into harmless ones and harmful ones according to their magnitude. Considering the impact of harmful shocks on temporal degradation performance, degradation rates as well as hard failure threshold levels, this paper proposes a new reliability model for systems subject to dependent competing failure processes. Hard failure occurs according to the combination of extended extreme shock model and extended δ -shock model, where the threshold level in the extended extreme shock model will be decreased by previous harmful shocks, and the threshold level in the extended δ -shock model depends on the magnitude of the previous harmful shock. Furthermore, each harmful shock will accelerate the degradation process by causing abrupt increase on degradation performance and acceleration on degradation rate. System reliability model is developed through analytical derivation and numerical calculation methods. Finally, a numerical study of RC pier columns of sea bridges is conducted to illustrate the implementation of the proposed model.